Image and myth : a history of pictorial narration in Greek art - Giuliani, Luca (The University of Chicago Press, 2013)
Covering the range of Greek style & its growth between the early Archaic & Hellenistic periods, this book explores the intellectual, social & artistic contextx in which the images in Greek art were created